Notohymena saprai sp. nov, a new oxytrichid ciliate (Protozoa, Ciliophora) from the Valley of Flowers, a Himalayan bioreserve region; description and morphogenesis of the new species - Kamra, Komal (Springer-Verlag, 2009)
A new oxytrichid ciliate Notohymena saprai sp. nov was isolated from the Valley of Flowers, an isolated bioreserve in the upper Himalayas. The ciliate was found in the soil samples collected from the peripheral areas of the flowering region of the valley which is covered with permafrost for nearly eight months in a year. Cells were excysted from the soil samples by the non-flooded petridish method. Species identification was performed by observations on live and silver-impregnated cells. Notohymena saprai sp. nov is highly flexible, measures 152 × 49 μm and shows abundant presence of dark green sub-pellicular granules. The species is distinct by virtue of its new combination of morphometric and developmental characters. Prominent distinguishing features of the new species are its relative large size and presence of four macronuclei (other species of this genus have two macronuclei). The study also reports morphogenetic peculiarities which separate it from the other known species of the genus.